2021
DOI: 10.1007/s11069-021-04908-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of emergency inter-organizational communication network under public health emergency: a case study of COVID-19 in Hubei Province of China

Abstract: Public health emergencies, especially major infectious diseases, may cause global crises. Timely and effective communication is essential for response to such incidents. However, the emergency response to such incidents usually lasts longer and break out repeatedly, and the existing static emergency communication network (ECN) analysis cannot fully reflect the dynamic information interaction between organizations during the emergency process. Therefore, this article takes the recent COVID-19 epidemic in Hubei,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…(2021b), which convincingly supports this study. Besides, a three-stage research framework was also adopted by Choi (2020) and Lu et al. (2021) based on pandemic development.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
See 3 more Smart Citations
“…(2021b), which convincingly supports this study. Besides, a three-stage research framework was also adopted by Choi (2020) and Lu et al. (2021) based on pandemic development.…”
Section: Discussion and Suggestionsmentioning
confidence: 99%
“…Currently, stage division standard has not been unified by scholars due to different time span investigated in different studies, which exists in three-stage division (Choi, 2020;Lu et al, 2021) and four-stage division perspectives. Nevertheless, these papers all divided the period according to pandemic development trends.…”
Section: Four Organization Collaboration Cn Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research suggested that emergency response networks tend to be decentralized over time. Lu et al constructed an emergency communication network by taking the COVID-19 outbreak in Hubei, China, as an example [ 48 ]. The study revealed the dynamics of emergency organizations and functions in their communication networks.…”
Section: Literature Reviewmentioning
confidence: 99%